Community Health and Wellness Principles of Primary Health Care - Clendon, J.; Munns, Ailsa (Elsevier, 2018)
The sixth edition of Community Health and Wellness has been fully revised and streamlined to incorporate contemporary thinking and research in community health and wellness from Australia, New Zealand and the global community.